Learning from Brexit: What parallels for decoupling from China? - Gary Clyde Hufbauer (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
Geopolitical decoupling is intended to, and generally succeeds in, reducing bilateral trade flows. But what about its impact on FDI? This Perspective examines the recent experience of UK FDI after Brexit, and Chinese FDI after Trump.
Keywords: 330